SHIPPING COST, SPOT RATE AND EBAY AUCTIONS: A STRUCTURED EQUATION MODELING APPROACH - Elhadary, Ossama (European Scientific Journal, ESJ, 2014)
In this paper, the author used a Structured Equation Modeling approach to capture the factors affecting selling prices of gold on eBay. The research showed that almost 99% of the variation in the auction’s selling price can be explained by the item’s calculated price (using the Gold daily spot rate). Auction prices of scrap Gold (per gram) was also found to be higher than that of useable gold. Though, unlike previous researches, shipping cost was not found to have any noticeable effect on the final auction price.